2022
DOI: 10.3390/life12101592
|View full text |Cite
|
Sign up to set email alerts
|

Why Has Digital Contact Tracing Worked Differently in Different Countries? Comment on Cao et al. The Impact of Digital Contact Tracing Apps Overuse on Prevention of COVID-19: A Normative Activation Model Perspective. Life 2022, 12, 1371

Abstract: I am writing you regarding your interesting article “The Impact of Digital Contact Tracing Apps Overuse on Prevention of COVID-19: A Normative Activation Model Perspective” [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Five scientific papers were published, including the editorial [ 2 , 4 , 5 , 6 , 7 ], equal to 27.8% of all the papers contained in the SI, which dealt with the topic of DH applied to contact tracing, the so-called digital contact tracing (DCT). These studies reported [ 4 , 5 ] and/or discussed [ 6 , 7 ] the impact of the DCT on the spread of the pandemic in different populations, together with the factors that influenced its use. The DCT, a new application of the DH, uses apps and various methods of tracking position and proximity, and it had a wide diffusion during the pandemic [ 2 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Five scientific papers were published, including the editorial [ 2 , 4 , 5 , 6 , 7 ], equal to 27.8% of all the papers contained in the SI, which dealt with the topic of DH applied to contact tracing, the so-called digital contact tracing (DCT). These studies reported [ 4 , 5 ] and/or discussed [ 6 , 7 ] the impact of the DCT on the spread of the pandemic in different populations, together with the factors that influenced its use. The DCT, a new application of the DH, uses apps and various methods of tracking position and proximity, and it had a wide diffusion during the pandemic [ 2 ].…”
mentioning
confidence: 99%
“…The published works on the DH, reported in the collection [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], demonstrate the usefulness of DH in connecting various branches of life sciences, especially during the pandemic. The use of DH in contact tracing has been particularly significant, with several studies reporting on its impact and factors influencing its use [ 2 , 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thank you for your comments [ 1 ] for our Manuscript. We would like to discuss with you the question, “Why has digital contact tracing worked differently in different countries?” from the perspective of national disaster cultures.…”
mentioning
confidence: 99%